The Effect of Imagery Training and Concentration on Forehand Serve Accuracy of the Junior Table Tennis Athletes - Maulana Arif Ardiyanto; Muhammad Furqon Hidayatullah; Sri Santoso Sabarini (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research aims to uncover: 1) the difference in the effect of internal imagery and external imagery on the forehand serve accuracy of the PTM Dwi Bengawan Solo players, 2) the difference in the effect of high concentration and low concentration on the forehand serve accuracy of Junior Table Tennis Athletes in Sukoahrjo, and 3) the interaction between training methods and concentration on the forehand serve accuracy of the Junior Table Tennis Athletes in Sukoharjo. This is an experimental research. The research samples were determined by using total sampling technique, while the total samples and population were 24 junior athletes in PTM Dwi Bengawan Solo. The data were collected using: 1) concentration test of PTM Dwi Bengawan Solo players and 2) forehand serve pretest. The research instrument included 2 tests, namely the forehand serve accuracy test with validity (0.809) and reliability (0.988). The concentration test with validity (0.89) and reliability (0.803). The data were analyzed using the two-way ANOVA with a significance level of α = 0.05. The results showed that: 1) There was a significant difference between internal imagery and external imagery training (p = 0.000 <0.05), so the internal imagery training method was better than external imagery. 2) There was a difference between players who had high concentration and low concentration (p = 0.000 < 0.05), so players who had high concentration were better than those who had low concentration. 3) There was an interaction between internal imagery and external imagery as well as high and low concentrations (p = 0.047 <0.05). Players who had high concentration would perform better if trained with internal imagery, while players who had low concentration would be better if trained with external imagery.